The role of wetland birds in biocultural conservation: analysing global discourses and practices on species and ecosystems - Araneda, Paola; Bridgewater, Peter; Pizarro, Jose Cristobal; Ibarra, Jose Tomas (My University, 2025)
Biocultural approaches for conservation weave knowledge systems of both Indigenous Peoples and Local Communities (IP&LCs) with scientific insights to address environmental justice and promote local and global sustainability. Enduring people-nature relationships, particularly through wetland birds, hold both ecological and cultural significance that can guide wetland conservation efforts. We conducted a systematic review of biocultural research literature published between 2000 and 2023, following PRISMA guidelines. This review identified 414 publications that addressed taxa, ecosystems, and biocultural discourses. The publications spanned 96 countries, with Mexico, the United States, and India having the highest numbers of studies. This is consistent with the ethnobotanical research tradition from the dominant anthropological discourse. Post-2010, an ethico-political dimension emerged from intergovernmental agreements and advocacy by IP&LCs, particularly from Latin America and Australasia. As essential socio-ecosystems and culturally significant taxa, wetlands and birds possess profound ecological and cultural values. The tangible and intangible meanings of wetland birds for IP&LCs highlight the importance of integrating biocultural approaches into conservation policies, strategies, and management to encompass diverse discourses, species, and ecosystems. Diversifying biocultural conservation discourses can address research and practice gaps, helping scholars and policymakers adapt to regional contexts, develop effective conservation strategies that support community welfare, and uphold IP&LC rights. By embracing diverse worldviews, conservation science and practice can become pluralizing and just, and assist thus the world in transformative change.
Keywords: rosemary hill; biocultural approaches to conservation; indigenous and local knowledge; wetland birds; discourses; human-bird relationships